Evaluation of the vector competence for Batai virus of native Culex and exotic Aedes species in Central Europe - Heitmann, Anna; Wehmeyer, Magdalena Laura; Lühken, Renke; Kliemke, Konstantin; Jöst, Hanna; Becker, Norbert; Helms, Michelle; Schmidt-Chanasit, Jonas; Jansen, Stephanie (Parasites & vectors, 2024)
Batai virus (BATV) is a zoonotic arbovirus of veterinary importance. A high seroprevalence in cows, sheep and goats and infection in different mosquito species has been observed in Central Europe. Therefore, we studied indigenous as well as exotic species of the genera Culex and Aedes for BATV vector competence at different fluctuating temperature profiles.
Gesehen am 11.11.2024